Stock Price, Trade Balance, and GDP: Interrelationships (Evidence from Indonesian Stock Exchange 2005- 2020) - Setya Ayu Rahmawati; Satia Nur Maharani (AIBPM Publisher, 2023)
This research’s focus are on the interrelationships between the three variables, namely the stock price, trade balance and GDP. Using 240 data quarterly between 2005-2020 using VECM Analysis. The results obtained show that in Indonesia Stock Exchange (IDX) there is no significant effect between the combined stock price and TB and vice versa. There is no significant two-way effect between stock prices and GDP. There was a significant influence between GDP on trade balance but not vice versa. The results of this study can enrich research in the field of macroeconomics and finance and can practically be a reference for observers for the Indonesian stock market.